Clinical implications of the cardio-ankle vascular index before and after transcatheter aortic valve implantation. Issue 5 (17th May 2023) - Miki, Yusuke; Tanaka, Akihito; Tokuda, Yoshiyuki; Tobe, Akihiro; Shirai, Yoshinori; Yuhara, Satoshi; Akita, Sho; Furusawa, Kenji; Ishii, Hideki; Mutsuga, Masato; Murohara, Toyoaki
Abstract : Background: Arterial stiffness indices are used to assess the material properties of the arterial wall and are associated with cardiovascular events. Aortic stenosis (AS) is commonly caused by degenerative calcification and can be associated with increased arterial stiffness. However, the clinical implications of arterial stiffness indices in AS patients before and after treatment are unknown. Methods: This single-center observational study enrolled 150 consecutive patients who underwent transcatheter aortic valve implantation (TAVI) for severe AS. The cardio-ankle vascular index (CAVI) was measured before and after TAVI. The patients were divided into two groups according to the CAVI values before and after TAVI: high CAVI group and low CAVI group. Patient and echocardiographic data and clinical outcomes, including cardiac death and hospitalization for heart failure (HF), were compared. Results: The pre- and postprocedural CAVI was 7.90 (6.75–9.30) and 9.65 (8.90–10.65), respectively. In the analyses with preprocedural CAVI, preprocedural echocardiographic aortic valve peak flow velocity was significantly lower in the high CAVI group. No significant differences between the two groups were observed in the occurrence of cardiac death or hospitalization for HF. In the analyses with postprocedural CAVI, B-type natriuretic peptide levels and E / e ′ ratio after TAVI were significantly higher in the high CAVI group. The composite of cardiac death and hospitalization occurrence for HF was significantly higher in the high CAVI group. Conclusion: CAVI before TAVI is mainly affected by the AS severity, while CAVI after TAVI is associated with left ventricular diastolic dysfunction and late cardiac events, which may reflect arterial stiffness.